2022
DOI: 10.1039/d1fo04303j
|View full text |Cite
|
Sign up to set email alerts
|

Maternal VD3supplementation during gestation improves intestinal health and microbial composition of weaning piglets

Abstract: Vitamin D3 (VD3) has been reported to improve the reproductive performance of sow. This study was conducted to investigate the long-term effect of maternal VD3 supplementation during gestation on the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Similar to a previous study [ 6 ], dietary VD 3 significantly increased the ADFI and ADG from 1 to 42 days and improved the FCR of the tested broilers from 43 to 63 days. The improved growth performance induced by VD 3 supplementation might act by promoting intestinal development and health through improving the status of the development of intestinal villi, promoting the activity of related digestive enzymes, and the intestinal antioxidant capacity, and maintaining the balance of intestinal flora [ 29 ]. In general, intestinal morphology is a key factor affecting the digestion and absorption of nutrients in poultry [ 30 ], and villus length, crypt depth, and the V/C ratio are significant indicators used to assess the maturity and functional capacity of intestinal tissues [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to a previous study [ 6 ], dietary VD 3 significantly increased the ADFI and ADG from 1 to 42 days and improved the FCR of the tested broilers from 43 to 63 days. The improved growth performance induced by VD 3 supplementation might act by promoting intestinal development and health through improving the status of the development of intestinal villi, promoting the activity of related digestive enzymes, and the intestinal antioxidant capacity, and maintaining the balance of intestinal flora [ 29 ]. In general, intestinal morphology is a key factor affecting the digestion and absorption of nutrients in poultry [ 30 ], and villus length, crypt depth, and the V/C ratio are significant indicators used to assess the maturity and functional capacity of intestinal tissues [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that dietary VD 3 addition had positive effects on animal carcass traits in broiler chickens [ 40 ] and pigs [ 29 ]. In Wenchang broilers, VD 3 supplementation reduced weight loss and improved the dressing percentage [ 40 ], while dietary VD 3 tended to decrease the body weight loss of sows during lactation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal nutrition during gestation is an important factor influencing the intestinal development of postnatal piglets. Numerous studies have elucidated that maternal dietary supplementation with specific nutrients, such as vitamin D3, galactooligosaccharides, 25-hydroxycholecalciferol, can improve the intestinal development and health of suckling piglets [ 45 , 46 , 47 ]. In the present investigation, the 0.15% Orn group was higher than the CON group in the jejunal and ileal villi height.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In the lactation phase, sufficient intake of colostrum and milk is a key factor in ensuring the intestinal health of piglets. [4][5][6] Previous studies have shown that the quality of a sow's milk is closely related to her diet during lactation. 2 Importantly, compelling evidence has indicated that immune agents and antioxidant protection can be transferred from mother to neonate via maternal colostrum and milk supply.…”
Section: Introductionmentioning
confidence: 99%